Nine- to fourteen-year follow-up of implant treatment. Part III: factors associated with periimplant lesions - Ann Marie Roos-Jansa°ker (journal of clinical periodontology, 2006)
Objective: The aim of the present paper was to analyse, on patient and implant basis, factors related to peri-implant lesions. Material and Methods: Two hundred and eighteen patients treated with titanium implants were examined for biological complications at existing implants 9–14 years after initial therapy. The effects of several potentially explanatory variables, both on patient and on implant levels, were analysed. Results: On the implant level, the presence of keratinized mucosa (p50.02) and plaque (p50.005) was associated with mucositis (probing depth X4mm1bleeding on probing). The bone level at implants was associated with the presence of keratinized mucosa (p50.03) and the presence of pus (po0.001). On the patient level, smoking was associated with mucositis, bone level and peri-implantitis (p50.02, o0.001 and 0.002, respectively). Peri-implantitis was related to a previous history of periodontitis (p50.05). Conclusions: Individuals with a history of periodontitis and individuals who smoke are more likely to develop peri-implant lesions.